Adaptação transcultural do MABC-2 e evidências de validade para o Transtorno do Espectro Autista na faixa etária de 11-16 anos - Quintas , Ricardo Henrique Rossetti (2020)
Autistic Spectrum Disorder (ASD) is looking for persistent compromises in the ability to initiate and sustain reciprocal social interaction and social communication with the presence of restricted, repetitive and inflexible patterns and behavior. Initial studies already described the unusual movements in people with ASD, however, with the advancement of research it became evident that these motor deficits were related to their atypical development and despite that, a motor assessment of this population is still a great challenge. The aim of this study was to carry out the crosscultural adaptation to the Brazilian Portuguese language of the MABC-2 Band 03 scale (11 to 16 years old) by analyzing the evidence of validity in people with ASD, identifying as a need and proposing adaptations in the application process, describing and correlating the motor profile with your cognitive profile using this new version. Method: The study was divided into three stages, stage 01: translation and adaptation of band 03 of the MABC-2 scale for our culture; stage 02: pilot study, evaluation and analysis by the committee of judges of the difficulties in applying the scale (n = 10) and application of adaptation suggestions (n = 10) and stage 03: evaluation of 23 adolescents with a medical diagnosis of ASD and correlation with cognitive profile. Results and Discussion: The translation and adaptation of the scale was performed by finding agreement levels between judges> 90% being considered satisfactory, as well as the aspects of validity and reliability where the stability and equivalence indices were ≥90% considered excellent with internal consistency ≥0.81 almost perfect. The experts' analysis verified the need to adapt the scale evaluation processes. The results of the two groups evaluated in step 2 were compared, observing better results for the evaluated group with the proposed adaptations for the execution of the play and catch 02 tasks (p =, 046), balance 03 (p =, 046) and in the percentile of play and catch (p =, 029), Balance (p =, 042) and in the GP (p =, 043) demonstrating that these processes can be effective for evaluating this population. The description of the motor profile pointed to significant motor impairments in most of the evaluated group, with 52.17% classified in the red zone, 4.34% in the Amber zone, with risk of developing motor impairment and 42.47% in the green zone, which is indicative of significant motor 11 impairment. In addition, mean positive correlations were found between overall performance and IQ (r =, 335, p = 0.49). Conclusion: it is concluded that the MABC2 scale can be used in our culture to evaluate people with ASD, with a better performance of the group evaluated with the adaptations. A heterogeneous motor capacity was observed in this population, with a wide range of functionality and impairment